Budaya Kerja dan Kompetensi Kerja: Kinerja Karyawan SPBU di Kabupaten Brebes - Mukson Mukson (Jurnal Manajemen Bisnis Performa, 2020)
ABSTRACT Improving good performance will create a good culture, if it can be achieved then otherwise the company must create an atmosphere of employees as assets must create a work culture that affects employee job satisfaction. However, employees must also have the work competencies required by the company, so that it is synergistic between employees and agencies or companies. The company's performance can be said to be of high quality and its objectives can be successfully achieved depending on the influence of the company's internal factors. This study aims to find out how the effect of changes in each variable on independent and dependent, both partially and simultaneously. Among others, the influence of work culture on employees' work results at gas stations Brebes district, the influence of work competencies on the work of employees at gas stations Brebes district, as well as the influence of work culture and work competencies to the work of employees at gas stations Brebes district. Researchers used quantitative approach methods with surveys and questionnaire instruments in the form of questionnaires. The population of this study is all gas station employees in Brebes District with a sample of 146 employees. Based on the calculation of the formula Slovin obtained a sample of 99 respondents. As a result, there is a significant influence between work culture and work competence on the performance of gas station employees in Brebes Regency. Keywords: Work culture, Work competence, Employee performance  ABSTRAKPeningkatan kinerja yang baik maka akan terciptanya budaya yang baik, apabila dapat tercapai maka sebaliknya perusahaan harus menciptakan suasana karyawan sebagai asset harus menciptakan budaya kerja yang mempengaruhi kepuasan kerja karyawan. Akan tetapi karyawan juga harus mempunyai kompetensi kerja yang dibutuhkan oleh perusahaan, sehingga saling sinergis antara karyawan dengan instansi atau perusahaan. Kinerja perusahaan dapat dikatakan berkualitas tinggi dan tujuannya dapat berhasil dicapai bergantung pada pengaruh faktor internal perusahaan. Penelitian ini memiliki maksud tujuan unuk mengetahui bagaimana efek perubahan yang ada pada masing-masing variabel terhadap independen dan dependen, baik secara parsial maupun simultan. Antara lain pengaruh budaya kerja kepada hasil kerja karyawan di SPBU kabupaten Brebes, pengaruh kompetensi kerja kepada hasil kerja karyawan di SPBU kabupaten Brebes, serta pengaruh budaya kerja dan kompetensi kerja kepada hasil kerja karyawan di SPBU kabupaten Brebes. Peneliti memakai metode pendekatan kuantitatif dengan survei dan instrumen angket dalam bentuk kuesioner. Populasi penelitian ini merupakan seluruh pegawai SPBU di Kabupaten Brebes dengan jumlah sampel 146 karyawan. Berdasarkan perhitungan rumus Slovin diperoleh sampel sebanyak 99 responden. Hasilnya terdapat pengaruh yang signifikan anatara budaya kerja dan kompetensi kerja terhadap kinerja karyawan SPBU di Kabupaten Brebes. Kata Kunci: Budaya kerja, Kompetensi kerja, Kinerja karyawan